Nilai-nilai Karakter Buku Bacaan Literasi Cerita Fiksi Siswa Sekolah Dasar - Juarsa, Osa; PGSD, Selvia; Dadi, Sri (JURIDIKDAS, 2024)
This study focuses on 18 character values that are sourced from the heart, thought, exercise and feeling/intention of the protagonist. The purpose of this research is to describe character values and to know the relevance of emerging character values to the development of elementary students. This type of research is qualitative research using a taxonomic approach. The research instrument in this research is the human instrument. The data collection technique used in this research ia a focused observation. The data analysis technique used the Spradley model, namely taxonomic analysis. Test the validity of the data in this study in the form of sources, namely fiction literacy reading book “Ayah yang Dirindukan”. The results showed that (1) the character values contained in fiction reading books were 13, namely: religious, honest, independent, responsible, creative, curious, love to read, communicative, social care, tolerance, work hard, rewards achievement, and loves peace (2) there is relevance or a related relationship between the character values that appear with the development of elementary students. Based on the results of the study, it can be concluded that there are thirteen character values in the literacy reading book “Ayah yang Dirindukan” and values that are relevant to the development of elementary students.